Management of post burn groin contracture: a case account - Narayan, Naveen; Gowda, Suhas Narayanaswamy; Nagraj, Ajay; Madhu, Abhigna; Venugopal, Vishnu (International Surgery Journal, 2021)
Similar to burns of the face, hands, and feet, groin and perineal burn injuries result in physical as well as psychosocial scarring for the patient. It often results in loss of functionality which is usually out of proportion to the percentage of burns. Hence, these burns are classified as major burns. Direct injury to the genitalia can lead to sexual dysfunction. In such circumstances, the treatment plan should comprehensively look into even psychosocial aspects of the patient. Both functional and cosmetic appearance should be the primary concern. With scarcely available burns unit and dedicated hospitals in India to treat burns, patients often develop severe contractures without proper post burns care. Most of the burn patients end up being treated by staff without special training in burn care. A variety of surgical procedures in post burn contractures of groin and perineum have been described all aimed to achieve satisfactory functional and cosmetic outcome. However, advantages of long-term care with regular physiotherapy, use of pressure garments, and massaging with emollient creams should not be overlooked and cannot be overemphasized. We present such a case of a young female with poor post burns care which resulted in post burn contracture of the groin and perineal area and had to endure with inconveniences. Patient was treated in our department adequately.